Sacrococcygeal teratoma type IV presenting with urine retention in infants - Tim Jumbi; Swaleh Shahbal; Francis Osawa; Fred Kambuni; Peter Mwika (Elsevier, 2018)
Background: Sacrococcygeal teratoma (SCT) is the commonest tumor in neonatal period. The type IV variant is a concealed presacral tumor which presents a diagnostic challenge as symptoms are only apparent due to the mass effects of the tumor. A common presentation is urine retention. We herein present two cases of patients with type IV tumors who presented with acute urinary retention with the aim of highlighting the challenges in diagnosis of the concealed tumor which apart from its malignant potential has serious obstructive effects on the urinary tract that can lead to irreversible kidney damage. Case presentation: We report two infants a 2 month old female and an 11 month old female who presented with acute urine retention. Both infants had been previously managed in peripheral facilities by urethral catheterization in an attempt to relieve the obstruction which remained persistent. On assessment at our facility both infants were noted to have a pre-sacral mass that was palpable on DRE and confirmed by CT scan. One infant had associated bilateral hydronephrosis from the obstructive effects of the mass on the urinary system. We used a combined abdominal and posterior sacral approach to resect the tumor in both patients with compete resolution of symptoms. Conclusion: SCT type IV presents a diagnostic challenge to the clinician due to its less apparent nature. Patients may present with urologic anomalies due to bladder outlet obstruction and in cases in which diagnosis is delayed, hydronephrosis and renal parenchymal disease may be an associated finding. Clinical assessment in infants presenting with urine retention and constipation of unknown origin should always include a digital rectal examination with particular attention to the posterior rectal wall which can reveal a presacral mass. Keywords: Sacrococcygeal teratoma type IV, Urine retention, Digital rectal examination